Economic analysis of oral dexamethasone for symptom relief of sore throat: the UK TOAST study - Burns, RM; Wolstenholme, JL; Jawad, S; Williams, N; Thompson, M; Perera, R; Hay, AD; Heneghan, C; Little, P; Moore, M; Hayward, G (BMJ Publishing Grou, 2018)
Objectives: To undertake an economic analysis assessing the cost-effectiveness of a single dose of oral dexamethasone compared with placebo for the relief of sore throat. Design: A UK-based, multicentre, two arm, individually randomised, double blind trial. Setting and Population: Adults (≥18 years) with acute sore throat and painful swallowing judged to be infective in origin, recruited and randomised in primary care. Intervention: a single dose of 10 mg oral dexamethasone compared with placebo given at primary care visit. Main Outcome: Incremental cost-effectiveness ratios (ICERs), cost per quality-adjusted symptom resolution using the EuroQol-five dimensions-five levels instrument, were estimated as part of a cost–utility analysis performed on an intention-to-treat cohort adopting a health payers perspective. Results: Differences in health-related quality of life (HRQoL) over 7 days from baseline and at 24 hours in the dexamethasone compared with the placebo group (2.9% and 2.5% higher, respectively) were observed. After controlling for the baseline HRQoL imbalances, the economic impact of the intervention was not statistically significant: the quality-adjusted life year difference was −0.00005 (95% CI −0.0002 to 0.00011) equivalent to a loss in HRQoL of a half hour in the dexamethasone group. The average cost per patient associated in the dexamethasone and placebo groups in the basecase analysis was £73 and £69, respectively. In the basecase probabilistic analysis, the mean ICER was −£6440 (95% CI −£132 151 to £126 335) and the median ICER was −£304 (IQR-£5816 to £3877); suggesting considerable uncertainty. Conclusions and relevance: The economic burden associated with sore throat is substantial and was estimated at £2.35 billion to the healthcare services payer based on reported resource use and 2015 UK unit costs. There is considerable uncertainty regarding the cost-effectiveness of a single dose of oral dexamethasone as a treatment strategy and therefore insufficient evidence to support its use in clinical practice.